Thromboxane Synthase Has the Same Pattern of Expression as Platelet Specific Glycoproteins during Human Megakaryocyte Differentiation - Vitrat, Natacha; Letestu, Rémi; Massé, Aline; Lazar, Vladimir; Vainchenker, William; Debili, Najet (Thrombosis and Haemostasis, 2000)
Regulation of the platelet formation process is poorly understood. It has been shown that p45NF-E2 deficient mice have a profound defect in platelet formation and recently the first platelet/megakaryocytic gene regulated by NF-E2, thromboxane synthase (TXS), has been identified. In this study, we investigated TXS expression as a model of a gene regulated by NF-E2 during MK differentiation. Megakaryocytic cells derived from blood CD34+ cells were purified according to their stage of maturation on the basis of expression of CD34, CD41a and CD42a, permitting to define different stages in MK differentiation. By means of real-time quantitative RT-PCR, we could determine that the level of TXS increased during differentiation in parallel with the expression of c-mpl and GPIIb (CD41). However, amounts of TXS transcripts increased about 1.6-fold more than that of GPIIb or c-mpl transcripts during maturation. Expression of TXS and MK specific proteins such as CD41a, CD42a and vWF was also correlated in maturing MKs. In addition, staining by anti-TXS antibody of proplatelet bearing MKs was not increased in comparison to that observed in mature MK, suggesting that TXS is not upregulated during platelet formation. In addition, we investigated whether TXS and cyclooxygenase could be involved in platelet formation by adding aspirin into the cultures. No significant decrease of platelet production was observed.In conclusion, this study shows that TXS is coordinately expressed with the other platelet proteins during MK differentiation but is not directly involved in platelet formation.
Keywords: Megakaryocyte; TXS